Atmiņas un uztveres analīze mentālajās kartēs: LU SZF gadījums - Zarečanska, Liene (Latvijas Universitāte, 2016)
Maģistra darbā „Atmiņas un uztveres analīze mentālajās kartēs: LU SZF gadījums” pētīta telpas uztvere un socio- emocionālais telpas vērtējums, kā teorētisko pamatu izmantojot R. Goledža telpisko enkurpunktu teoriju un mentālo karšu teoriju, kas tiek atzītas par telpiskās kognīcijas pamatteorijām. Analizējot enkurpunktu teoriju un mentālo karšu teoriju, tika uzstādīts uzdevums izdalīt būtiskākos telpisko reprezentāciju, atmiņu un uztveri ietekmējošos aspektus un pētīt to saistību ar telpas uztveri. Darba novitāte ir saistāma ar telpiskās uztveres un mentālo karšu pētniecību LU SZF esošo un bijušo studentu uztverē un atmiņā.

The aim of the thesis “Analysis of memory and perception in mental maps: the case of Faculty of Social Sciences, University of Latvia” was to research the spatial perception and socially-emotional space assessment, taking a basis of R. Golledge’s the Anchor- point theory and the Mental maps theory, which are regarded as core research theories in the spatial cognition. While analysing the Anchor-point theory and the Mental maps theory, the goal to discover the most important aspects that are influencing spatial representation, memory and perception and their connection with spatial perception, was set. Novelty of the research is related to investigation of the spatial perception and analysis of the mental maps in the audience of existing and former students of the Faculty of Social Sciences, University of Latvia. In the research part of the thesis the categorisation of background objects to researched space – Faculty of Social Sciences, University of Latvia, spatial cognition and the socially-emotional assessment and representation of the spatial cognition in mental maps were analysed.
Analysis of memory and perception in mental maps: the case of Faculty of Social Sciene, University of Latvia
Keywords: Komunikācijas zinātne; telpiskā kognīcija; telpa; uztvere; atmiņa; mentālās kartes